2020
DOI: 10.1007/978-3-030-55536-8_10
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon Stocks from Peat Swamp Forest and Oil Palm Plantation in Central Kalimantan, Indonesia

Abstract: Conserving high carbon density tropical peat forests is one of the most cost-efficient strategies for climate change mitigation at national and global levels. Over past decades, large areas of tropical peat forests have been converted to oil palm plantation in Indonesia resulting in significant carbon emissions into the atmosphere. Here, we quantified the ecosystem carbon stocks in a total of six sites: two primary peat swamp forest sites, one secondary peat swamp forest site, and three young oil palm plantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Peat depth varied in forest plots from less than 50 cm at the plot closest to the river to almost 3 m at the plot located farthest from the river. The plot closest to the river (FOR-1) was a 30-year-old secondary forest, managed as an agroforestry garden before Tanjung Puting National Park was established in 1982 and communities were moved across the Sekonyer river (Novita et al, 2020; according to interviews with community members). FOR-1 vegetation was dominated by pioneer species such as Macaranga motleyana (Euophorbiaceae), Buchanania sessifolia (Anacardiaceae), Baccaurea stipulate (Phyllanthaceae), and Litsea firma (Lauraceae) (Novita et al, 2020).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peat depth varied in forest plots from less than 50 cm at the plot closest to the river to almost 3 m at the plot located farthest from the river. The plot closest to the river (FOR-1) was a 30-year-old secondary forest, managed as an agroforestry garden before Tanjung Puting National Park was established in 1982 and communities were moved across the Sekonyer river (Novita et al, 2020; according to interviews with community members). FOR-1 vegetation was dominated by pioneer species such as Macaranga motleyana (Euophorbiaceae), Buchanania sessifolia (Anacardiaceae), Baccaurea stipulate (Phyllanthaceae), and Litsea firma (Lauraceae) (Novita et al, 2020).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The plot closest to the river (FOR-1) was a 30-year-old secondary forest, managed as an agroforestry garden before Tanjung Puting National Park was established in 1982 and communities were moved across the Sekonyer river (Novita et al, 2020; according to interviews with community members). FOR-1 vegetation was dominated by pioneer species such as Macaranga motleyana (Euophorbiaceae), Buchanania sessifolia (Anacardiaceae), Baccaurea stipulate (Phyllanthaceae), and Litsea firma (Lauraceae) (Novita et al, 2020). The other two forest plots (FOR-2, FOR-3) were primary forests dominated by Vatica oblongifolia (Dipterocarpaceae) and Santiria apiculate (Burseraceae) (Novita et al, 2020).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical peatland forests provide numerous ecosystem services including carbon storage, and thus they are important for climate change mitigation (Murdiyarso et al 2009;Novita et al 2021). However, in this study, it was found that aboveground carbon storage of peatland forest particularly in standing trees was signi cantly altered by land use conversion.…”
Section: Changes In Aboveground Carbon Stocksmentioning
confidence: 54%
“…The litter in tropical peat swamp forest is composed predominantly of woody debris, coarse and fine roots, and leaf litter (Miyajima et al, 1997), contributing a remarkable portion for total and heterotrophic respiration on the surface (Hirano et al, 2009;Sundari et al, 2012), also similar within the mineral soil rainforest (Zhou et al, 2013). However, different species are grown as primary plants and understory cover in oil palm plantations (Sabiham et al, 2012;Ashton-Butt et al, 2018;Novita et al, 2020). Peatland monoculture ecosystem sequestered C with a broad range (Khasanah et al, 2015;Novita et al, 2020), releasing heterogeneous C sources ranging from pruned palm fronds with high lignin content (Moradi et al, 2014;Pulunggono et al, 2019) to the easily degraded understory cover material (Amatangelo and Vitousek, 2009).…”
Section: Introductionmentioning
confidence: 99%